HUBUNGAN USIA, JENIS KELAMIN DAN TINGKAT PENDIDIKAN ORANG TUA TERHADAP PENGETAHUAN SWAMEDIKASI PEMBERIAN PARACETAMOL PADA ANAK - Farmasita, Rizky; Veronica, Arbella (Jurnal Insan Farmasi Indonesia, 2024)
According to the National General Health News about child health, it is known the prevalence of fever  reaches 33.4%. This makes parents need to take an active role in self-medication efforts to treat children who have a fever. This study aims to evaluate the relationship between age, gender, and level of education with knowledge of self-medication in administering paracetamol to children. The non- experimental research method with a cross-sectional design uses a descriptive approach based on questionnaire data. Data were analyzed statistically using the chi-square test. The study was conducted in Depok, the area of Grand Depok City. The population and sample of the study were parents in Grand Depok City, with 196 respondents. The results of the analysis showed that the majority of respondents were aged 40-59 years, female (147 people), educated in high school/vocational school, employed as private employees (98 people), and had one child (91 people). The level of knowledge  of respondents about paracetamol self-medication is good, with 51% knowing the correct dosage. The  conclusion of the study there is no significant relationship between the demographic of parents and knowledge of self-medication.